Pengaruh Pendidikan, Paritas, Pengetahuan, Persepsi Terhadap Sikap Menyusui Pada Ibu Bekerja Di Instansi Pemerintah (Studi Di SKPD Propinsi Jawa Timur) - Maria Ratnawati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2013)
One of the determinant discontinued of exclusive breastfeeding practices is working mother. Factors of working mothers are initiation, workplace factor and social support. The study analyzed determinant of exclusive breastfeeding practice among working mothers such as mother’s behavior; facilities and workplace factors; and social supports.This cross sectional study collected using self-administered questionnaires by respondents. The number of samples was 56 working mothers who have 6-24 month children. The result was analyzed using logistic regression. Results showed that knowledge affect attitude; parity affect subjective norm, but none of them significantly affecting self efficacy. self-efficacy affect initiation. Result of multivariate analysis determined exclusive breastfeeding among working mothers were employee and co-worker support, maternity leave, and chances given to breast pump. The East Java Government was recommended to implementation of the government role such as allow mother flexible time to express breast milk, supporting lactation room in the workplace and a refrigerator and giving maternity leave until 3 month after postpartum.